Pancreatic metastases from ocular malignant melanoma: the use of endoscopic ultrasound-guided fine-needle aspiration to establish a definitive cytologic diagnosis: a case report. (December 2016) - De Moura, Diogo; Chacon, Danielle; Tanigawa, Ryan; Coronel, Martin; Cheng, Spencer; Artifon, Éverson; Jukemura, José; De Moura, Eduardo
Abstract Background When encountering solid pancreatic lesions, nonpancreatic primary metastases are rare and differentiating a metastasis from a primary neoplastic lesion is challenging. The clinical presentation and radiologic features can be similar and the possibility of a pancreatic metastasis should be considered when the patient refers to a history of a different primary cancer. Endoscopic ultrasound offers a key anatomical advantage in accessing the pancreas and endoscopic ultrasound-guided fine-needle aspiration has become the gold standard method for diagnosing pancreatic lesions. Case presentation A 58-year-old white Hispanic woman with a history of uveal malignant melanoma, presented with abdominal pain and jaundice. On admission, laboratory tests were performed (her total bilirubin was 6.37 mg/dL with a direct fraction of 5.30 mg/dL). Cross-sectional, abdominal computed tomography with contrast, showed a low-attenuating lesion localized in the pancreatic head (measuring 4 × 3 cm) and a thinner section of the distal bile duct suspicious for compression. Our patient was scheduled for an endoscopic ultrasound-guided fine-needle aspiration to establish a diagnosis. Endoscopic ultrasound showed a solid, hypoechoic, well-defined lesion with regular contours (measuring 3.17 × 2.61 cm), localized between the head and neck of the pancreas. Endoscopic ultrasound-guided fine-needle aspiration was performed with a 22G needle and cytology confirmed the diagnosis of metastatic melanoma. Our patient subsequently underwent right orbital exenteration, followed by duodenopancreatectomy without complications. At the moment our patient is receiving adjuvant chemotherapy at an outside oncology clinic. Conclusions To the best of our knowledge, this is a very rare presentation of an ocular malignant melanoma with an isolated pancreatic metastasis causing symptomatic biliary obstruction. Endoscopic ultrasound-guided fine-needle aspiration has proven to be the best method to diagnose solid pancreatic lesions. In this particular case, cytology was essential in confirming the diagnosis and guiding the most adequate therapy, which was a pancreatic resection, ocular exenteration of the melanoma, followed by adjuvant chemotherapy.